2009
DOI: 10.1007/s10570-008-9273-x
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of isotropic and anisotropic liquid droplets dispersed in a cellulose liquid crystalline derivative

Abstract: In this work we study the strain-induced deformation of both isotropic and anisotropic liquid droplets dispersed in a liquid crystalline cellulose matrix. We have produced two types of acetoxypropylcellulose (APC) solid films one with a droplet dispersion of the commercial liquid crystal E7 from Merck, and another with a droplet dispersion of silicone oil. To produce the solid films a solution of APC (60%wt) in dimethylacetamide (DMAc) with 15%wt of either the commercial nematic liquid crystal E7 or the silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Five independent successful measurements were performed with the longest dimension of the sample parallel or perpendicular to the casting shear direction. The features (not the values) of the stress/strain curves obtained were similar to those from other APC and HPC already reported in the literature (Borges et al 2001;Almeida et al 2009). …”
Section: Mechanical Setupsupporting
confidence: 88%
See 1 more Smart Citation
“…Five independent successful measurements were performed with the longest dimension of the sample parallel or perpendicular to the casting shear direction. The features (not the values) of the stress/strain curves obtained were similar to those from other APC and HPC already reported in the literature (Borges et al 2001;Almeida et al 2009). …”
Section: Mechanical Setupsupporting
confidence: 88%
“…Their different preparation methods generate materials with different mechanical, optical, thermal and structural properties (Siqueira et al 2010). Because of this, cellulose derivative have been widely used as reinforcing agents in bio and nano composites (Liu et al 2011;Siqueira et al 2010), electro-optical displays materials (Godinho et al 1998;Almeida et al 2002;Costa et al 2007), local strain sensor (Almeida et al 2009) and biocarrier.…”
Section: Introductionmentioning
confidence: 99%
“…The features (not the values) of the stress/strain curves obtained were similar to those from other APC and HPC already reported in the literature for isotropic and anisotropic cellulose derivatives [ 59 , 60 , 61 ].…”
Section: Liquid Crystalline Cellulose Network Characterized By DIsupporting
confidence: 85%
“…The liquid crystalline behavior of cellulose derivatives has since aroused much interest in the field of liquidcrystalline polymers (Bhadani and Gray 1983;Isogai et al 1984;Pawlowski et al 1987;Yamagishi et al 1988;Chen et al 1992;Jiang and Huang 1993;Shaikh et al 1999;Huang et al 2007;Godinho et al 2009;Almeida et al 2009). During recent decades, several studies reported the introduction of the bulky and rigid mesogenic substituents on the cellulose backbone as side groups (Terbojevich et al 1999;Wu et al 2002Wu et al , 2003Wu et al , 2004Granström et al 2009).…”
Section: Introductionmentioning
confidence: 99%